2010
DOI: 10.1111/j.1744-6570.2010.01191.x
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Ingroup and Outgroup Preference: A Longitudinal Causal Investigation

Abstract: Although there has been substantial research on perceptions of preference in hiring, there is considerably less focus on perceptions of preference in organizational activities more generally. Researchers seldom assess perceptions of preference for both historically high-and low-status groups and for both one's own group and others. Using a three-wave longitudinal survey of 1,094 employees, the causal direction between perceived preference and satisfaction with management, moderators of that relationship, and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 82 publications
0
8
0
Order By: Relevance
“…Therefore, if organizations can create a supportive diversity climate, racial minorities are more likely to respond with greater perceived psychological safety and performance behaviours. Conversely, for Whites, a positive diversity climate and psychological safety hold less value than for racial minorities (Merritt et al ., ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, if organizations can create a supportive diversity climate, racial minorities are more likely to respond with greater perceived psychological safety and performance behaviours. Conversely, for Whites, a positive diversity climate and psychological safety hold less value than for racial minorities (Merritt et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Racial identity theory (RIT) further provides a fine‐grained analysis of the importance racial minorities place on positive organizational contexts (McKay et al ., ; Phinney, ). According to RIT, racial minorities tend to identify more with their race than Whites and react more strongly to discrimination and prejudice at work (Merritt, Ryan, Mack, Leeds, & Schmitt, ). Minority employees may feel more psychologically unsafe in reaction to a diversity climate where they are not included and valued by the organization.…”
Section: Introductionmentioning
confidence: 99%
“…A key argument explaining the effects of pro-diversity practices on individual and organizational outcomes draws on social identity theory (Tajfel and Turner, 1986): minority groups tend to perceive themselves and be perceived as out-group organizational members because access to key positions and resources in the organization has been historically controlled by majority groups (Merritt et al, 2010). Pro-diversity practices are implemented to foster cultural minorities' feelings of being integrated or included as organizational members, without damaging the in-group status of employees of the majority group.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the wealth of research investigating relationships between PD and various organizational outcomes, scholars have yet to explore fully physical withdrawal as an outcome of PD. In fact, this relationship has been examined in only a handful of published studies (e.g., Merritt, Ryan, Mack, Leeds, & Schmitt, 2010). A review of these studies has shown that the PD−physical withdrawal effect has been inconsistent.…”
mentioning
confidence: 99%